Middle and Late Holocene paleotemperatures reconstructed from oxygen isotopes and GDGTs of sediments from Lake Pupuke, New Zealand - Heyng, Alexander; Mayr, Christoph; Lücke, Andreas; Moschen, Robert; Wissel, Holger; Striewski, Bernd; Bauersachs, Thorsten (Quaternary international, 2015)
Quantitative Holocene temperature reconstructions for Southern Hemisphere terrestrial environments are still restricted to few records, and multi-proxy methods are rarely applied to the same system. Here, we test the applicability and comparability of temperature reconstructions inferred from different methodological approaches. We combined sedimentary cellulose and diatom oxygen isotope data from Lake Pupuke (North Island New Zealand) to derive a record of lake water temperatures. This record is complemented with mean annual air temperatures derived from the branched GDGT index MBT measured on the same sedimentary record. The datasets of both reconstructions show little temperature variation for the period 1320e7110 cal. BP. The exceptions are a warmer period culminating between 1700 and 1600 cal. BP reflected in both proxies and centennial-scale intervals with cooler water temperatures at 3380 and 2750 cal. BP recorded in the oxygen-isotope-based temperature reconstruction but not in the MBT-inferred air temperature estimates. We suggest that variations in lake circulation are the likely reason for deviations between temperature reconstructed from different proxies.
Keywords: Paleotemperatures; New Zealand; Holocene; Oxygen isotopes; Biogenic silica; Branched GDGTs